Viable but non-cultivable bacteria and their implications for microbiological safety - Jiménez-Moleón MC; Solano-Gómez JA (Open Journal of Environmental Biology - Peertechz Publications, 2022)
Bacteria are microorganisms found in all environments and they fulfill various tasks in ecosystems, however, some can affect the human population causing outbreaks of disease and death.